1987
DOI: 10.1104/pp.83.4.732
|View full text |Cite
|
Sign up to set email alerts
|

Action of Proline on Stomata Differs from That of Abscisic Acid, G-Substances, or Methyl Jasmonate

Abstract: MATERIALS AND METHODS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 10 publications
3
41
1
Order By: Relevance
“…5B). This result is in disagreement with previous findings showing complete or almost complete stomatal closure in epidermal peels of Commelina benghalensis and Nicotiana glauca treated with either MeJA or ABA (Raghavendra and Reddy, 1987;Suhita et al, 2003). Our data are also in conflict with the report demonstrating that 10 mM of either MeJA or ABA equally and effectively reduce the stomata aperture in Ler (Suhita et al, 2004).…”
Section: External Application Of 12-opda Promotes Stomatal Closurecontrasting
confidence: 57%
“…5B). This result is in disagreement with previous findings showing complete or almost complete stomatal closure in epidermal peels of Commelina benghalensis and Nicotiana glauca treated with either MeJA or ABA (Raghavendra and Reddy, 1987;Suhita et al, 2003). Our data are also in conflict with the report demonstrating that 10 mM of either MeJA or ABA equally and effectively reduce the stomata aperture in Ler (Suhita et al, 2004).…”
Section: External Application Of 12-opda Promotes Stomatal Closurecontrasting
confidence: 57%
“…Measurements of K+ content in Commelina guard cells with ionsensitive electrodes have also shown discrepancies between K+ concentrations and measured osmotic potentials, leading to the suggestion that sucrose could be an additional source of osmoticum (18). Increases in sugars have also been correlated with opening in experiments with epidermal peels (29,31). Both import of sugars from the mesophyll (3,25,26) and starch interconversion (40) have been invoked as sources for the osmotically active sugars.…”
Section: Discussionmentioning
confidence: 99%
“…Glycinebetaine may reduce stomatal opening and decrease the transpiration rate, thus leading to the decrease in Na + accumulation in shoots (Raghavendra and Reddy, 1987). Rahman et al (2002) observed that root tips and root cap cells of rice plants treated with GB alone produced numerous vacuoles, which did not develop in the control plants.…”
Section: Discussionmentioning
confidence: 99%